2021
DOI: 10.3390/ani11040969
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Duration of Farrowing Crate Closure on Physical Indicators of Sow Welfare and Piglet Mortality

Abstract: This study examines effects of opening hinged farrowing crates 4 or 7 days post-farrowing. Sows (n = 696) allocated to 3 treatments: PC—crate closed, T4—crate opened day 4, and T7—crate opened day 7 were assessed for body condition score (BCS), lameness, shoulder lesions and teat lesions. Piglet mortality was higher in T4 (27.8%) compared to T7 (23.9%) and PC (25.9%) (p < 0.05) which did not differ with T7 (p > 0.05). No difference in risk of being laid on was found 1–3 days post-farrowing with all crate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…They also showed that different temporary crating pen designs may have different effects on body lesions. Ceballos et al ( 17 , 18 ) did not find any effect of crate opening (on D4 or D7) on udder and body lesions or lameness until weaning, compared to farrowing crates. However, the authors reported less teat and udder lesions in the third week post-partum in sows housed in TC compared to sows remaining in closed crates.…”
Section: The Interpretation Of Pig Welfare In Different Farrowing Sys...mentioning
confidence: 92%
See 4 more Smart Citations
“…They also showed that different temporary crating pen designs may have different effects on body lesions. Ceballos et al ( 17 , 18 ) did not find any effect of crate opening (on D4 or D7) on udder and body lesions or lameness until weaning, compared to farrowing crates. However, the authors reported less teat and udder lesions in the third week post-partum in sows housed in TC compared to sows remaining in closed crates.…”
Section: The Interpretation Of Pig Welfare In Different Farrowing Sys...mentioning
confidence: 92%
“…Similarly, Moustsen et al ( 46 ), with 55 sows per treatment, found no improvement in survival when comparing release on D4 or D7. However, Ceballos et al ( 18 ) did find a significant difference in mortality when comparing TC until D4 or D7 with 161–185 sows per treatment, although with an atypically high overall mortality level (27.8 vs. 23.9% mortality).…”
Section: Management Choices In Temporary Crating Systemsmentioning
confidence: 94%
See 3 more Smart Citations